Interpretation of fractional flow reserve in ST-elevation myocardial infarction culprit lesions. Issue 6 (September 2015) - Hoole, Stephen P.; Brown, Adam J.; Jaworski, Catherine; McCormick, Liam M.; Clarke, Sarah C.; West, Nick E.J.
Abstract : Background: Pressure wire assessment of the infarct-related artery (IRA) in ST-elevation myocardial infarction (STEMI) is not recommended until microcirculatory dysfunction recovers. Objective: The objective of this study was to assess serial fractional flow reserve (FFR) and the index of microcirculatory resistance (IMR) in the IRA of STEMI patients to better understand and interpret FFR during primary percutaneous coronary intervention (PPCI). Methods: Forty-one patients undergoing PPCI for STEMI were studied with a pressure wire at baseline after thrombectomy and after stenting. Results: The majority of STEMI culprit lesions in the IRA were haemodynamically significant (mean FFR pre-PPCI: 0.54±0.20); only 4/41 culprit lesions had FFR greater than 0.80. The FFR of the culprit lesion and the initial IMR were correlated ( r =0.45, P =0.004). Patients with a normal initial IMR of less than 25 exhibited lower culprit lesion FFR values (0.47±0.20 vs. 0.60±0.18, P =0.03) despite milder angiographic stenoses [angiographic stenoses (%): 80.4±10.4 vs. 86.6±8.0, P =0.03] but showed a reduction in the IMR during PPCI (pre-PPCI: 16.9±5.7 vs. post-PPCI: 32.2±22.6, P =0.009). Conclusion: STEMI culprit lesions are haemodynamically significant. A subset of STEMI IRAs has initially preserved microcirculatory function; thus, the culprit stenosis may feasibly be assessed through FFR.